2012
DOI: 10.1111/j.1525-1594.2012.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Decompression During Venoarterial Extracorporeal Membrane Oxygenation for Left Ventricular Failure in Children: Current Strategy and Clinical Outcomes

Abstract: From 2005 to 2011, 23 of 178 (12.9%) patients with venoarterial (VA) extracorporeal membrane oxygenation (ECMO) had left atrial (LA) decompression to help improve left ventricular (LV) function, LA/LV dilatation, and/or lung edema. LA decompression was achieved with LA cannulation (n = 16), surgically created adjustable atrial septal defect (n = 3), or balloon atrial septostomy (n = 4). Sixteen (70%) patients had LA decompression at the time of ECMO initiation and all had LA decompression within 12 hours of EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 13 publications
2
85
0
2
Order By: Relevance
“…Pulmonary edema secondary to left ventricular distension may subside by venting of the left atrium [37][38][39][40]. Adding a veno-venous component for a veno-venous arterial configuration may be indicated in case of concomitant pulmonary disease.…”
Section: Arterial Blood Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary edema secondary to left ventricular distension may subside by venting of the left atrium [37][38][39][40]. Adding a veno-venous component for a veno-venous arterial configuration may be indicated in case of concomitant pulmonary disease.…”
Section: Arterial Blood Gasesmentioning
confidence: 99%
“…Some authors have suggested the concomitant use of intra-aortic balloon pump or microaxial pump to decrease the LV afterload [44][45][46][47][48][49]. When severe pulmonary edema is present, left atrial venting has been proven effective to alleviate pulmonary congestion [37][38][39][40]45,50].…”
Section: Pulmonary Artery Catheter/cardiac Output Measurementmentioning
confidence: 99%
“…This is particularly true when there is increased cardiac return (e.g., systemic pulmonary collaterals), which is common in the pediatric population. Adequate decompression of the systemic ventricle is of critical importance for myocardial recovery (36).…”
Section: Short-term Vad Supportmentioning
confidence: 99%
“…Early LA decompression was reported to enhance LV recovery. 2 A few methods of achieving LA decompression have been reported, including balloon atrial septostomy, 3,4 combined blade and balloon atrial septostomy, 5 trans-septal/transaortic LV sheath, 6-8 transaortic pigtail LV drain, 9 surgical LA/LV vent and trans-septal cannula incorporated into ECMO. 10, 11 However, the experience with these is mostly limited to children.…”
mentioning
confidence: 99%
“…In this setting, both the wall stress and the oxygen consumption of the LV increase, and recovery of LV function and weaning from ECMO will be delayed. 2 Although not all patients on ECMO suffer from the described vicious circle, this complex medical condition does demand a solution to avoid additional complications.…”
mentioning
confidence: 99%